Luis Martín Santos est-il (vraiment) existentialiste ? - Thierry Capmartin (Cahiers de Civilisation Espagnole Contemporaine)
Time and again, Luis Martín Santos reaffirmed his moral and intellectual attachment, indeed his admiration, for the figure of Jean-Paul Sartre. But must we inevitably conclude that the sense that his works –and first and foremost Tiempo de silencio– was of existentialist inspiration, as has often been put forward? In this present study, this question will be examined anew, with the help of the oblique light which Santos’ little studied psychiatry texts can shed. In the end, it is the relevance of the category of «existentialism» within the field of the history of literature that we intend to question more generally, using a quite singular case as a starting point.